Ekfraza jako pytanie o prawo do zachwytu - Zieliński, Jan (Colloquia Litteraria, 2014)
Ekphrasis as a question about the right to enchantment The author discusses Fr. Janusz S. Pasierb’s poem spotkanie [meeting] from Zdejmowanie pieczęci [Removing the seal] volume (Warsaw, 1982). He treats the poem as an example of a double ekphrasis – a simultaneous reference to two works of art; one of them is Auguste Ottin’s large sculpture Polyphème surprenant Galatée dans les bras d’Acis (1866) composed into Marie de’ Medici’s fountain in Parisian Jardin du Luxembourg, the other Giovanni Lafranco’s painting Lucina e Norandino sorpresi dall’Orco (c. 1624) from the Borghese Gallery in Rome. The analysis, which evokes mythological, literary (Ariosto, Proust) and iconographical (Redon) contexts, leads to a conclusion about art’s mediating role; about art as ground that allows for enchantment over otherwise inaccessible forms of beauty.